A new species of Gonionemus (Hydrozoa: Limnomedusae) from southern Australia - Watson, Jeanette E.; Govindarajan, Annette F. (Zootaxa, 2017)
A new species of a crawling limnomedusa belonging to the genus Gonionemus (Hydrozoa: Limnomedusae: Olindiidae) was collected from the brown alga Cystophora monilifera in an intertidal rock pool in Western Port, Victoria, Australia. The new species is described and compared with the three known species of Gonionemus. The mitochondrial DNA barcode markers cytochrome oxidase I and 16S rRNA were sequenced and compared to sequences from other olindiid species. The sequencing results corroborate the morphological findings.